Rohdea henryi, the replacement name for R. chinensis, and a new combination for its variety (Asparagaceae) - Tanaka, Noriyuki (Phytotaxa, 2019)
Rohdea Roth (1821: 196) is a genus of Asparagaceae Jussieu (1789: 40, as Asparagi), comprising 20 or a few more species distributed in temperate to subtropical regions of Bhutan, China, India, Japan, Laos, Myanmar, Nepal, Taiwan, Thailand, and Vietnam (Tanaka 2010, Averyanov et al. 2014, 2017, Tanaka et al. 2018). Traditionally, Rhodea has often been included in Convallariaceae Link (1829: 184) (e.g. Takhtajan 1997, Tanaka 2003), a group of plants that are treated by Chase et al. (2009) as subfamily Nolinoideae within Asparagaceae.